An updated patent review of glutaminase inhibitors (2019–2022). (2nd January 2023) - Wang, Danni; Li, Xiaohong; Gong, Guangyue; Lu, Yulong; Guo, Ziming; Chen, Rui; Huang, Huidan; Li, Zhiyu; Bian, Jinlei
ABSTRACT: Introduction: Kidney-type glutaminase (GLS1), a key enzyme controlling the hydrolysis of glutamine to glutamate to resolve the 'glutamine addiction' of cancer cells, has been shown to play a central role in supporting cancer growth and proliferation. Therefore, the inhibition of GLS1 as a novel cancer treating strategy is of great interest. Areas covered: This review covers recent patents (2019-present) involving GLS1 inhibitors, which are mostly focused on their chemical structures, molecular mechanisms of action, pharmacokinetic properties, and potential clinical applications. Expert opinion: Currently, despite significant efforts, the search for potent GLS1 inhibitors has not resulted in the development of compounds for therapeutic applications. Most recent patents and literature focus on GLS1 inhibitors IPN60090 and DRP104, which have entered clinical trials. While other patent disclosures during this period have not generated any drug candidates, the clinical update will inform the potential of these inhibitors as promising therapeutic agents either as single or as combination interventions.